Simplicial structures in topology - Ferrario, Davide L; Piccinini, Renzo A. 1933 (New York Springer, 2010)
Simplicial Structures in Topology provides a clear and comprehensive introduction to the subject. Ideas are developed in the first four chapters. The fifth chapter studies closed surfaces and gives their classification. The last chapter of the book is devoted to homotopy groups, which are used in a short introduction on obstruction theory. The text is more in tune with the original development of algebraic topology as given by Henri Poincaré (singular homology is not discussed). Illustrative examples throughout and extensive exercises at the end of each chapter for practice enhance the text. Advanced undergraduate and beginning graduate students will benefit from this book. Researchers and professionals interested in topology and applications of mathematics will also find this book useful
Preface -- Fundamental Concepts -- Simplicial Complexes -- Homology of Polyhedra -- Cohonology -- Triangulable Manifolds -- Homotopy Groups -- Bibliography -- Index.
Keywords: Topology